Processamento correferencial em idosos com e sem a doença de Alzheimer - Alves, Giorvan ânderson dos Santos (2012)
This research, entitled Coreferential Processing by the Elderly Subjects With and Without Alzheimer's Disease, aimed to analyze and compare the coreferential processing by the elderly subjects with and without Alzheimer's disease (AD) in Brazilian Portuguese. To achieve our goals and respond to our hypotheses, we supported on the Mini-Mental State Examination (MMSE) in order to classify the dementia degree affecting the AD elderly subjects and to qualify the level of understanding, enabling them to respond to the on-line tests. We used the self-paced reading technique and we selected 12 elderly subjects without pathologies (ESWP), and 06 elderly subjects with Alzheimer's Disease (ESAD), a total sample of 18 subjects. As results of the first experiment, we found, in the ESWP group, pronouns being processed faster than repeated names, which agrees with studies on adults without pathology in Brazilian Portuguese (LEITÃO, 2005; QUEIROZ, LEITÃO, 2008; LEITÃO, SIMÕES, 2011). And in the ESAD group, volunteers were faster when retrieving the repeated name, confirming the findings that have been found in literature regarding the pathologies that have some impairment of the working memory (ALMOR et al., 2000) and (ALBUQUERQUE, 2008). In order to analyze the level of semantic impairment in subjects with AD mild impairment during coreferential processing, we carried out a second experiment which focuses on the coreference processing from retrievals with hypernyms and hyponyms. Results showed that the elderly control group preferred, during the anaphoric retrieval, the superordinate NPs. But the elderly subjects with Alzheimer's disease showed no significant differences between conditions (hyponym and hyperonym). We concluded that it is apparent that pronouns and hypernyms are processed more quickly by the elderly subjects without pathologies because they contain less semantic features required to identify their antecedents; and the repeated names as well as hyponyms are processed more slowly because they contain more semantic features. In the AD elderly subjects cases, we believe that the lack of significant difference between hyponyms and hypernyms, in this kind of anaphoric retrieval, is resulting from the impaired working memory, featuring that the AD elderly subjects need that words be restated as activating that memory.